RESEARCH OF CONSUMERS ATTITUDES ON THE ORGANIC FOOD CONSUMPTION IN THE SERBIAN ENCLAVES IN KOSOVO - Maksimović, Goran; Milošević, Božidar; Jovanović, Radomir (Economics of Agriculture, 2017)
The organic production in Serbian enclaves in Kosovo has a great potential based on the extensive production mostly in hilly-mountainous areas with rich and convenient environment for the organic production of medicinal plants, fruits, vegetables, wine, honey etc., but it still keeps developing. The enclave can realise a high income, and thereby also an economic basis for the sustainable development of multifunctional agricultural holdings in Serbian enclaves, by the production and sale of organic products on local markets. In this paper, the authors study the consumers attitudes on purchase and consumption of organic food in Serbian enclaves in Kosovo. Empirical research was carried out on a spatial sample of 300 respondents, by a personal communication technique using the questionnaire as an instrument of research method. Areas of research are towns: Northern KosovskaMitrovica, Leposavic, ZubinPotok and Gracanica. Goal of the research is to discover the preferences, motives, attitudes and interests of consumers for buying the organic products, based on a defned survey to recognise the basic features of supply and the demand of organic agricultural and food products. After analysing the conducted survey, we have discovered that the organic food market in Serbian enclaves in Kosovo has not been suffciently developed; it is necessary to expand the range of organic agriculture products and a constant supply is required, better marketing, and better information and education of consumers in order to raise supply to a higher level.